Oxytocin and vasopressin inhibit hyper-aggressive behaviour in socially isolated mice. (15th September 2019) - Tan, Oliver; Musullulu, Hande; Raymond, Joel S.; Wilson, Bianca; Langguth, Mia; Bowen, Michael T.
Abstract: Despite the high prevalence of aggression across a wide range of disorders, there is a severe lack of pharmacological treatments. Recent rodent studies have shown both centrally and peripherally administered oxytocin is effective in reducing territorial aggression, an adaptive form of aggression not reflective of pathological hyper-aggression. The current study tested i.p. administered oxytocin and vasopressin in a model of non-territorial hyper-aggression and examined the involvement of oxytocin receptors (OXTR) and vasopressin V1a receptors (V1aR). Male Swiss mice (N = 160) were either socially isolated or group housed for 6 weeks prior to the commencement of testing; wherein two unfamiliar weight and condition matched mice were placed into a neutral context for 10 min. Socially isolated mice exhibited heightened aggression that was powerfully and dose-dependently inhibited by oxytocin and vasopressin and that was accompanied by dose-dependent increases in close social contact (huddling) and grooming. These anti-aggressive effects of oxytocin were blocked by pre-treatment with a higher dose of selective V1aR antagonist SR49059 (20 mg/kg i.p.), but not a lower dose of SR49059 (5 mg/kg i.p.) or selective OXTR antagonist L-368, 899 (10 mg/kg i.p.). This is consistent with a growing number of studies linking a range of effects of exogenous oxytocin to actions at the V1a receptor. Interestingly, the highest dose of the OXTR agonist TGOT (10 mg/kg) also reduced isolation-induced aggression. These results suggest that while activation of the V1a receptor appears critical for the anti-aggressive effects of oxytocin, activation of the oxytocin receptor cannot be excluded. This article is part of the Special Issue entitled 'Current status of the neurobiology of aggression and impulsivity.' Highlights: Social isolation induced aggression in mice models pathological human aggression. We tested the anti-aggressive effects of oxytocin and vasopressin. Oxytocin and vasopressin powerfully inhibited isolation induced aggression. Oxytocin and vasopressin increased close social contact and grooming. Pre-treatment with a V1aR antagonist, but not an OXTR antagonist, blocked oxytocin effects.